Does overcrowding and health insurance type impact patient outcomes in emergency departments? - Pedro de Araujo; Maroula Khraiche; Andrea Tukan (Health Economics Review, 2013)
We examine the impact of Emergency Department (ED) overcrowding on wait times and patient outcomes using a unique cross section of about 32,000 patients for an ED located in the Southwestern United States. We construct a measure of a patient's outcome and estimate the extent to which it is worsened by long waits in the ED. We find that waiting at an ED due to overcrowding tends to generate a negative outcome for all patients. We also find that this negative outcome is larger for those on Medicaid or who have no insurance and smaller for those with private insurance or Medicare.
Keywords: I12; I13; 330; Emergency Department; Overcrowding; Instrumental Variable Probit Model